‘Well-worn grooves’: Music, materiality and biographical memory - Taylor, Iain A. (Popular Music History, 2020)
Recorded music, as both aesthetic listening experience, and as material culture, has a deep mnemonic resonance for a great many people. Starting from Csikszentmihalyi’s (1993) theorization on the significance of artefacts in the structuring of ‘well-worn grooves’ of consciousness, this article considers the biographical function of the metaphorical (and literal) ‘well-worn grooves’ of music-based artefacts such as records. Building upon existing arguments from material culture studies and popular music studies, this article uses excerpts from research interviews with self-identified ‘music enthusiasts’ to argue that an attentiveness to the complex and intertwined relationships between popular music listening, and its materiality, presents possibilities for looking beyond a broadly canonic understanding of popular music history, arguing for a greater attentiveness to the richness of individual music-based biographies as a means of exploring the relationship between popular music and the past.